Analisis Peningkatan Pelayanan Stasiun Bogor Terhadap Kepuasan Pengguna Jasa Kereta Api Dengan Metode Importance Performance Analysis (IPA) - Riyanto, Azhar Hermawan; Riyanto, Bambang (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Excellent service is part of the target PT. Kereta Api Indonesia (Persero) to maximize efforts in innovation services, one of which implementation is the existence of Bogor Station, This study uses a quantitative approach, according to the basic assumptions axiology quantitative approach seeks explanation of the relationship between the variables studied, while the research method used is descriptive analysis, which aims to explain or describe further the pattern of correlation, the relationship between two or more variables studied, technique of analysis by analyzing the performance of services with Servqual Service, methods of science and CSI and utility station facilities in terms of user services based on standards Minimum service station where respondents are users of services in Bogor Station. Based on the analysis we can conclude CSI scores of this study is 62%, which indicates the overall service of Bogor Station are included in the category quite satisfied and there are five attributes that a top priority for immediate improved performance, among others, the availability of the number of toilets, availability and comfort of the lounge (waiting room) passengers, cleanliness and comfort toilet, comfort and ease up/down passenger (Peron) and the availability of information and the announcement of train travel.